Cooling multi-family residential units using natural ventilation in the Central U.S. - Rai, Roby (Kansas State University, 2016)
The use of Natural Ventilation (NV) to cool buildings in mixed climates can conserve significant cooling energy. In mixed climates it is particularly important during the fall and the spring, where appropriately designed buildings should use very little energy for heating or cooling. Natural ventilation is also important in residential buildings, where internal heat gain can be managed, making cooling by natural ventilation easier. Earlier investigations have clearly shown the economic, social, and health benefits of the use of NV in built environment. Studies have shown that increased airflow or air-speed during ventilation can bring a significant rise in comfort range which further reduces the cooling energy required to maintain comfort. The climatic data of the central United States (U.S.) shows that the availability of frequent high speed wind and favorable seasonal humidity conditions make natural ventilation feasible in late spring and early fall, where NV can offset most of the cooling demand for a home or multifamily residential unit, though it is not possible to maintain thermal comfort during the entire summer with NV alone. In mixed climates, NV for multifamily residential units has not been investigated thoroughly. According to 2009 International Residential Code, multifamily residential buildings are typically designed to use a code minimum amount of operable or ventilating windows, 4% of the floor area being ventilated, while also using lightweight construction methods (such as wood framing) that is prone to fast thermal response during the overheated periods of the year. While climate may favor the use of NV in these building types, the sizing of windows and the building construction type limit the potential to save energy with NV. This study hypothesized that the maximum benefits from NV in the climate of the central U.S. requires further optimization of window openings beyond the energy code minimum, and a construction system incorporating mass that can slow thermal response during overheated periods. During the study, the climatic data of the central US was scrutinized to understand the most suitable time frames where NV could be applied in order to maintain indoor thermal comfort in various construction systems in residential buildings: mainly lightweight using wood framing, and heavier construction using concrete and masonry. The location of the housing unit, first level or second level, was also examined to account for the differences in thermal gains and losses as a result of ground coupling and additional heat gain from the roof. Further, computational fluid dynamics evaluated the comfort achieved with different ventilation areas. Change in comfort hours by using NV tested the practicability of the use of NV to maintain indoor thermal comfort for different scenarios. The study concluded with design recommendations for building orientation, operable window size, and construction type as these factors relate to thermal comfort and the optimization of multifamily residential buildings to utilize NV for energy savings in the U.S.
Keywords: Natural ventilation; Cooling; Passive cooling; Residential building design; Energy conservation; Central U.S.